Influência do estado nutricional nas características vocais, função pulmonar e força muscular respiratória de crianças - Pascotini, Fernanda Santos (2014)
Objective: assess the influence of nutritional status and waist circumference in vocal characteristics, lung function and respiratory muscle strength in children aged between eight and ten years. Methods: participated in the study scolars, of both sexes, aged between 8 and 10 years of public school in Santa Maria-RS. After the anthropometric classification and assessment of nutritional status by BMI Z-score, the children were divided into 3 groups: eutrophic, overweight and obese. We conducted evaluation of vocal characteristics (maximum phonation time – (MPT), sound pressure level - SP and acoustic analysis - the Multi-Dimensional Voice Program Advanced Kay Pentax ®), lung function (spirometry) and respiratory muscle strength (manovacuometry) - MIP / MEP. For statistical analysis, we used frequency distribution, mean and standard deviation, median and 1st and 3rd quartile, the Shapiro-Wilk test, ANOVA, Scheffepost test, Kruskall-Wallis test and Pearson Correlation Exact. Results: The study included 82 children, 53.7 % were female, aged between 8 and 10 years (mean 9.2 ± 0.8 years), 46.4 % eutrophic, 26.8 % were overweight and 26, 8 obese. The larger the abdominal circumference (AC), greater forced vital capacity (FVC) (p = 0.003). Regarding the CA group with percentile between 25 and 75 had longer sustain the vowels / e / and / a / in TMF and higher MEP (p <0.05). Have the CA with ≥ 75 had higher SP (p = 0.003). No statistically significant difference in FVC, MPT, MIP, MEP, SP and acoustic variables in relation to nutritional status variables was found. There is a strong correlation between: /a/ MPT and MPT /e/ (0.84), the amplitude perturbation quotient (APQ) and noise-harmonic ratio (NHR) (0.79), APQ and Frequency Variation (vf0) (0.71), MEP and MIP (0.66), NHR and vf0 (0.68), APQ and the pitch perturbation quotient (PPQ) (0.60), PPQ and NHR (0.50), the voice turbulence index (VTI) and APQ (0.45), vf0 and PPQ (0.43), NHR and VTI (0.37), NHR and Amplitude Variation (vAm) (0.31). The other correlations were moderate or weak. Conclusion: It can be concluded that nutritional status in children 8-10 years of age does not influence lung function (FVC), the efficiency of the laryngeal and respiratory coordination (MPT), respiratory muscle strength (MIP and MEP) and vocal acoustic features, as well as pressures not interfere with the respiratory acoustic vocal characteristics. However, the CA is localized fat, can positively affect pulmonary function.